Erythropoietin mediates re-programming of endotoxin-tolerant macrophages through PI3K/AKT signaling and protects mice against secondary infection - Zhang, Xue; He, Dan; Jia, Jialin; Liang, Feihong; Mei, Jie; Li, Wenhua; Liu, Tingting; Wang, Zhiyu; Liu, Yu; Zhang, Fengxue; Zhang, Zhiren; Luo, Bangwei (Frontiers in Immunology, 2022)
Initial lipopolysaccharide (LPS) exposure leads to a hypo-responsive state by macrophages to a secondary stimulation of LPS, known as endotoxin tolerance. However, recent findings show that functions of endotoxin-tolerant macrophages are not completely suppressed, whereas they undergo a functional re-programming process with upregulation of a panel of molecules leading to enhanced protective functions including antimicrobial and tissue-remodeling activities. However, the underlying molecular mechanisms are still elusive. Erythropoietin (EPO), a glycoprotein regulated by hypoxia-inducible factor 1α (HIF-1α), exerts anti-inflammatory and tissue-protective activities. Nevertheless, the potential effects of EPO on functional re-programming of endotoxin-tolerant macrophages have not been investigated yet. Here, we found that initial LPS exposure led to upregulation of HIF-1α/EPO in macrophages and that EPO enhanced tolerance in tolerized macrophages and mice as demonstrated by suppressed proinflammatory genes such as Il1b, Il6, and Tnfa after secondary LPS stimulation. Moreover, we showed that EPO improved host protective genes in endotoxin-tolerant macrophages and mice, such as the anti-bacterial genes coding for cathelicidin-related antimicrobial peptide (Cnlp) and macrophage receptor with collagenous structure (Marco), and the tissue-repairing gene vascular endothelial growth factor C (Vegfc). Therefore, our findings indicate that EPO mediates the functional re-programming of endotoxin-tolerant macrophages. Mechanistically, we found that PI3K/AKT signaling contributed to EPO-mediated re-programming through upregulation of Irak3 and Wdr5 expression. Specifically, IL-1 receptor-associated kinase 3 (IRAK3) was responsible for inhibiting proinflammatory genes Il1b, Il6, and Tnfa in tolerized macrophages after LPS rechallenge, whereas WDR5 contributed to the upregulation of host beneficial genes including Cnlp, Marco, and Vegfc. In a septic model of mice, EPO pretreatment significantly promoted endotoxin-tolerant re-programming, alleviated lung injury, enhanced bacterial clearance, and decreased mortality in LPS-tolerized mice after secondary infection of Escherichia coli. Collectively, our results reveal a novel role for EPO in mediating functional re-programming of endotoxin-tolerant macrophages; thus, targeting EPO appears to be a new therapeutic option in sepsis and other inflammatory disorders.